Heat stress detection and mitigation in feedlot cattle - Unruh, Ellen M. (Kansas State University, 2017)
Feedlot cattle frequently endure high environmental temperature-humidity index conditions in the summer months within cattle feeding regions of North America. Heat stress develops when the total heat gain (combined effects of environmental and metabolic factors) exceeds an animal’s heat loss capabilities. The objective of my research was evaluating heat mitigation strategies and developing a practical method to identify animals that are of greatest risk of heat stress; thus improving animal welfare and performance. A number of heat abatement strategies have been utilized in US feedlots including shade, sprinklers, nutritional modifications, and misters. A literature review was performed using published journal articles demonstrated significant benefits of providing shade to feedlot cattle. Sprinkling the pen surface may be just as beneficial as sprinkling or misting cattle. Sprinkling the ground not only cooled the ground which increased the thermal gradient between lying cattle and the ground, but also provided increased thermal conductivity and better heat flow down that gradient. A study was performed to develop a noninvasive, remotely applied, practical method to identify animals at risk for heat stress. Infrared thermography images were obtained during the morning hours and pant scores obtained in the afternoon hours. Data mining techniques were employed to evaluate accuracy of potential classification methods to identify heat stress events in the afternoon based on the known morning data. Using infrared technology as a diagnostic test was not accurate for predicting heat stress events in the study presented. Finally a retrospective study of Kansas feedlot performance, medical and weather data was performed. Findings indicate that diagnostic counts of bovine respiratory disease are associated with elevated ambient temperature two days prior. In conclusion, heat stress in beef feedlot animals is an important area of research. Heat mitigation methods such as shade have been proven to be effective at reducing heat stress in beef feeder cattle. Further research is needed to evaluate the use of infrared technology to predict heat stress events in the feedlot setting.
Keywords: Veterinary medicine; Heat stress; Feedlot; Bovine respiratory disease